ДОСЛІДЖЕННЯ ЕКСПЕРИМЕНТАЛЬНОГО ЗРАЗКА БЕЗДРОТОВОГО ЗАРЯДНОГО ПРИСТРОЮ ЕЛЕКТРОМОБІЛЯ - Павлов, В.Б.; Подольцев, О.Д.; Павленко, В.Є. (Інститут електродинаміки НАН України, Київ, 2021)
A prototype of a wireless charger of inductive type with serial resonance in the circuits of the transmitting and receiving coils has been developed and manufactured, and experimental studies of the efficiency of power transmission from an external source to a storage battery have been carried out. It is shown that the efficiency of the created sample takes values in the range 39% - 78 % and depends on the operating frequency and the distance between the coils. It is also shown that when using coils with an outer diameter of 500 mm, the positioning of these coils in the process of charging the battery at a distance of up to 10 cm does not lead to a significant decrease in efficiency. The experimental values of the efficiency are compared with the calculated ones obtained on a simplified model that takes into account only resistive losses in the coils, and it is shown that the experimental values of the efficiency are 15-20 % less than the calculated ones. References. 8, figures. 5, table 1.